1972
DOI: 10.1530/acta.0.0700665
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Castration and Starvation Upon Pituitary and Serum Levels of Luteinizing Hormone and Follicle Stimulating Hormone in Male Rats

Abstract: Serum and pituitary levels of luteinizing hormone (LH) and follicle stimulating hormone (FSH) were measured by radioimmunoassay in intact and castrated juvenile (21 days) and adult male rats. The effect of total starvation upon the gonadotrophin response to castration was also investigated in adult animals. In rats castrated at 21 days of age, serum and pituitary levels of LH were elevated by 7 days and increased progressively for 4 weeks. Serum concentrations of FSH also increased within 7 days and remained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

1973
1973
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 0 publications
3
21
1
Order By: Relevance
“…Root and Russ (1972) reported that gonadal removal resuited in similar concentrations of pituitary and(or) serum LH and follicle stimulating hormone (FSH) in rats that received diets restricted in energy and in rats fed ad libitum. The data from the present study agree with the previous observation in that the pituitary in the nutritionally induced, anestrous heifer has the ability to secrete LH in high concentrations following gonadal removal.…”
Section: Discussionmentioning
confidence: 99%
“…Root and Russ (1972) reported that gonadal removal resuited in similar concentrations of pituitary and(or) serum LH and follicle stimulating hormone (FSH) in rats that received diets restricted in energy and in rats fed ad libitum. The data from the present study agree with the previous observation in that the pituitary in the nutritionally induced, anestrous heifer has the ability to secrete LH in high concentrations following gonadal removal.…”
Section: Discussionmentioning
confidence: 99%
“…Acute starva tion of adult male rats has been shown to lead to a decreased release of at least five anterior pituitary hormones [8] including LH (30% reduction in 24 h [9]). The starva tion-induced deficiencies in serum LH con centrations were partially [10] or complete ly [9,11] overridden following castration. Furthermore, hypothalamic content [12] and stimulated release [11] of LHRH were unaf fected by starvation.…”
Section: Introductionmentioning
confidence: 95%
“…It is well known that starvation affects reproductive activity in various vertebrates including birds (Hosoda et al ., 1955;Morris and Nalbandov, 1961;Vigersky et al ., 1977;Brake and Thaxton, 1979;Glass and Swerdloff, 1980;Hoffer et al ., 1986). It is also known that the suppressive effect of starvation on reproduction is mediated by a reduction of gonadotropin secretion (Negro-Vilar et al ., 1971;Root and Russ, 1972;Howland and Skinner, 1973;Stewart et al ., 1973;Howland, 1975;Scanes et al ., 1976;Campbell et al ., 1977;Tanabe et al ., 1981;Badger et al ., 1985;Hoshino et al ., 1988;Foster et al ., 1989;Xie, 1991), and that gonadotropin secretion increases again during re-feeding (Howland, 1975;Tanabe et al ., 1981;Hoshino et al ., 1988;Xie, 1991).…”
Section: Introductionmentioning
confidence: 99%